Ways to go? (Un)sustainable school commuting in Majorna, Gothenburg city. Issue 1 (31st December 2023) - Knutsson, Beniamin; Hellberg, Sofie
ABSTRACT: Gothenburg city has bold ambitions of becoming carbon neutral. School commuting is one piece of the puzzle in reducing emissions. While the literature on school transportation is extensive, the issue of climate change has been overlooked. This article explores how parents in the district of Majorna understand mundane choices of school transportation in a context of increasing recognition of climate change. The article shows that school transport is a contentious issue, entangled with subjectivity, emotions, and notions of responsibility. The findings also highlight some complexities: (1) Although most parents are concerned with climate change it is not a significant factor in daily transportation. (2) There is a discourse in favour of active transportation where climate change is explicitly downplayed, on the other hand regular car use merges with deep climate concerns. (3) Informants' anticipations of future urban traffic conflict with their hopes, yet it seems difficult to imagine something otherwise.